Do Liquidity, Firm Size, and Gender Diversity Influence Property and Real Estate Sector Profitability (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the face of global economic uncertainty and property market fluctuations, companies in the property and real estate sector are required to maintain profitability. This sector contributes significantly to the national GDP, but it has also faced pressure due to declining demand and instability in the growth of the real estate sector's GDP from 2021 to 2024. Profitability is a key indicator of a company's sustainability, influenced by various internal factors such as liquidity, firm size, and gender diversity in leadership. The target population of this inquiry encompasses property and real estate enterprises enumerated on the Indonesia Stock Exchange throughout the 2021–2024 interval. Through the application of purposive sampling, a total of 52 data observations were delineated as the empirical sample. The dataset was subjected to scrutiny employing multiple linear regression procedures facilitated by SPSS software version 26. The empirical outcomes substantiate that liquidity, firm size, and gender diversity simultaneously influence profitability. Partially, liquidity has a positive and significant effect on profitability, while gender diversity has a negative and significant effect. In contrast, firm size does not have a significant influence on the profitability of property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2024 period.